Effectiveness of Pfizer/BioNTech and Sinopharm COVID-19 vaccines in reducing hospital admissions in prince Hamza hospital, Jordan - Al-Momani, Hafez; Aldajah, Khawla; Alda'ajah, Ebtisam; ALjafar, Yousef; Abushawer, Zainab (Frontiers in Public Health, 2022)
Background There is a need to establish the effectiveness of the coronavirus disease 2019 (COVID-19) vaccines in reducing COVID-19-related hopitalization of patients in Jordan. As the vaccination program accelerates, it is important to determine whether the vaccines’ effectiveness (VE) has successfully reduced the number of acute cases admitted to hospital. Methods To determine the efficacy of Pfizer-BioNTech and Sinopharm COVID-19 vaccines among Jordanian patients admitted to Prince Hamza hospital in Jordan, a single center case-control study was performed. The study analyzed the hospitalization rates of vaccinated (n=536) and unvaccinated (n=585) individuals across the two-month period from February 6 to April 6, 2022. The cases were patients who tested positive for SARS-CoV-2 (‘case-patients’), whilst the control group were hospital patients who did not test positive for SARS-CoV-2 (‘control-patients’). Results This study found that among 1121 total participants (561 cases and 560 control), the overall vaccine effectiveness (VE) among the participants was 84% (95% Cl 79%–88%). VE was higher in females (88%, 95% Cl 84% to 93%) than in males (77%, 95% Cl 67%–84%) (p<0.001), and it was highest in those between the ages of 18 and 28-years-old (95%, 95% CI 86%–98%). For patients with pre-existing conditions, including chronic heart disease, chronic lung disease, and diabetes, VE was higher compared to patients with no comorbidities, though the difference was not statistically significant. Finally, in comparing all vaccinated participants, VE was higher for those who received the Pfizer vaccine (VE = 92%, 95% CI 88%–94% (OR 0.08, 95% CI 0.06–0.12) than for those who received the Sinopharm vaccine (VE = 67%, 95% CI 52%–78%) (OR 0.33, 95% CI 0.22–0.48); (p = 0.011). Conclusion Overall, Pfizer and Sinopharm vaccines were found to be effective in limiting hospitalizations for acute cases of coronavirus among Jordanian adult’s patient’s cohort between February 6 and April 6, 2022, especially among patients with comorbidities.